The Impact of Globalization of Technology on Treatment and Care Systems For People with Mental Disorders - Budi Raharjo, Sri; Pranawa, Burham; Sutarni, Nanik; Wiedhar Saputri, Ananda Megha (Asian Journal of Social and Humanities, 2024)
Globalization is a traditional process of exchanging world paradigms for the work, understanding and aspects of local wisdom of a nation which encourages the emergence of a situation of mutual dependence (interdependence) for technological, economic, health, social and cultural activities. Health globalization is closely related to economic and social globalization as a phenomenon to describe something that is complex or consists of various interrelated elements, such as for example in psychology which describes individual traits or characteristics that cannot be simplified. These changes have an impact on citizens in general and individuals, causing a complex influence on the incidence and causes of mental disorders in population development. In addition, the ways in which mental disorders are understood and shaped by ongoing global shifts. This problem is also possible with increasing industrialization and urbanization, access to western traditions to medical systems will become more common and sophisticated as a shift that can lead to changes in health technology. Internet access is a form of technological progress that cannot be avoided and will influence philosophical, ideological and political views of the world. The prevalence of mental disorders is closely related to social, economic and cultural conditions. If we consider all the previously mentioned changes in information technology, we can easily predict that the form and content of mental disorders, psychological treatments and psychotherapy as well as pharmacotherapy will undergo serious changes. Considering developments in the current era of globalization of modern technology and increasingly fierce competition in society, it is possible that people are not strong enough to live their lives so they can experience mental disorders and it needs to be underlined that mental illnesses can attack anyone.